Whole-body cryotherapy as a recovery technique after exercise: A review of the literature - Rose, C.; Edwards, K. M.; Siegler, J.; Graham, K.; Caillaud, C. (International Journal of Sports Medicine, 2017)
This review aims to evaluate the current body of literature investigating the effect of whole body cryotherapy on recovery after exercise. A systematic search was conducted to investigate the effect of whole body cryotherapy (WBC, exposure to temperatures between -110 to -190°C) on markers of recovery after damaging exercise in healthy, physically active subjects. Of the 16 eligible articles extracted, ten induced muscle damage using controlled exercise in a laboratory setting, while six induced damage during sport-specific training. Results indicated that muscle pain was reduced in 80% of studies following WBC. Two applied studies found recovery of athletic capacity and performance with WBC improved, variables of this nature were also improved in 71% of studies using controlled exercise. Further benefits of WBC treatment included reduction of systemic inflammation and lower concentrations of markers for muscle cell damage. These results suggest that WBC may improve recovery from muscle damage, with multiple exposures more consistently exhibiting improvements in recovery from pain, loss of muscle function, and markers of inflammation and damage. The diversity in muscle damage protocols, exposure timing with regards to exercise, as well as temperatures, duration and frequencies of exposure, make specific recommendations preliminary at present.